Landscape identity: Approaches to its conceptualisation, capture and integration into place branding processes - Falco Knaps; Sylvia Herrmann; Tanja Mölders (Spatial transformation: Processes, strategies, research design, 2022)
The integration of spatial identity is seen to be a crucial factor for successful place branding. However, spatial identity is often insufficiently conceptualised. In light of this, this article presents a theory-based approach to using spatial identity in an applied context such as place branding. This is done using the example of the Regiobranding research project. This project systematically surveyed landscape identity - a specified variant of spatial identity. Starting from social-constructivist approaches to landscape, landscape identity is presented as an individual and social interpretation of landscape distinctiveness and character and the associated place attachments. In the empirical part, individual interpretations of landscape identity are qualitatively recorded in a rural case study region and evaluated across all the cases. This cross-case analysis visualises the appropriated identity-forming landscape, in other words, the reference points that are repeatedly interpreted as distinctive or characteristic in relation to the space and/or that are frequently activated as components of individual place attachments. The results show an extensive range of different reference points: those interviewed describe these reference points in various ways, connect them, and use them as cognitive/emotional reference points. Furthermore, the cross-case analysis revealed contradictory patterns of interpretation. Our empirical findings highlight that landscape identity is predominantly an individually constructed reality, which is neither unambiguous nor without contradictions. Against this background, specific actions are recommended for using landscape identity in place branding processes.
urn:nbn:de:0156-08911407; hdl:10419/251347; https://econpapers.repec.org/RePEc:zbw:arlfob:19
Keywords: 710; Spatial identity; landscape identity; place branding; spatial planning